Therapeutic Effects of Alpha-Lipoic Acid on High-Dose Ibuprofen-Induced Renal Damage in Rats - Tozak Yıldız, Halime (The European Research Journal, 2026)
Objectives: Nonsteroidal anti-inflammatory drugs, particularly ibuprofen, are commonly used worldwide and can cause nephrotoxicity through prostaglandin inhibition, oxidative stress, and inflammatory activation. This study aimed to investigate the histopathological, fibrotic, and oxidative effects of high-dose ibuprofen administration and to evaluate the therapeutic potential of alpha-lipoic acid) in reversing these changes. Methods: Twenty-eight male Wistar albino rats were randomly divided into four groups (n=7): Control, Alpha-lipoic acid (100 mg/kg), Ibuprofen (250 mg/kg), and Ibuprofen+Alpha-lipoic acid. Ibuprofen was administered orally for 21 days, while alpha-lipoic acid was given during the last 7 days. Histopathological changes were evaluated using Hematoxylin & Eosin, Masson’s Trichrome, and Periodic Acid–Schiff staining. Fibrotic and inflammatory markers (TGF-β1, α-SMA, TLR-4) were assessed immunohistochemically. Oxidative stress was evaluated by measuring malondialdehyde levels and superoxide dismutase activity. Results: Ibuprofen administration resulted in significant tubular degeneration, hydropic changes, necrosis, tubular dilatation, and hyperemia. Masson’s Trichrome staining showed a significant increase in collagen deposition, while Periodic Acid-Schiff staining revealed glomerular and tubular basement membrane thickening. Immunohistochemistry demonstrated marked upregulation of TGF-β1, α-SMA, and TLR-4 (P